Increasing Financial Resources for Public Higher Education: International Experiences and Suggestions for Vietnam - Linh, Nguyen Thuy; Dinh, Nguyen Van; Huong, Nguyen Mai; Hiep, Pham Hung (VNU Journal of Science: Education Research, 2021)
Increasing financial resources has been regarded as one of the particular importance of the current higher education development in Vietnam, notably public universities. These groups of higher education institutions are facing challenges as their main sources of funding - state allocation - are declining gradually. In this study, the authors examine the mechanisms employed in other countries across the world to improve financial resources for their higher education institutions. Thus, some implications are withdrawn for public higher education institutions in Vietnam.